KAJIAN GEOTEKNIK UNTUK PERENCANAAN PEMBANGUNAN PEMUKIMAN BARU KAWASAN CEMPAKA, KABUPATEN KOTAWARINGIN TIMUR, KALIMANTAN TENGAH - Maranatha Manik; Muhammad Ikhwan Yani; Suradji Gandi (Fakultas Teknik Universitas Palangka Raya, 2025)
The area development of Cempaka, Kotawaringin Timur District, Central Kalimantan is increasing rapidly, especially considering the increasing population growth. One of the steps that needs to be taken to reduce the risk in developing the area is to conduct geotechnical studies. This study aims to determine the type, physical properties, and mechanical properties of the soil, determine the appropriate foundation based on the soil conditions, and provide engineering recommendations to increase the soil bearing capacity within the study area. The methods applied in the study are including sampling, disturbed and undisturbed, using hand drill, geotechnical mapping, and sondir test. Bore samples were prepared for soil physical properties test. The soil types at the study sites were peat deposits, clay, and silt clay, which is saturated, expansive, very soft - hard consistency, and no water outflow from the pores. The value of qu based on sondir data at depth of 1 - 6 m, equal to 56,80 - 66,32 ton/ m2 , and qa equal to 18,93 - 22,11 ton/ m2 , while value of qu based on laboratory data equal to 0,65 - 2 , 48 ton/ m2 , and qa equal to 0,22 - 0,83 ton/ m 2 . Technical engineering recommended to increase the carrying capacity of the soil, is to use cerucuk foundation for the foundation of the house, and the use of geotextiles and the addition of urugan land on the road residing in the neighborhood.